Hands-On GUI Programming with C++ and Qt5 : Build stunning cross-platform applications and widgets with the most powerful GUI framework. - Zhi Eng, Lee (Packt Publishing, 2018)
Qt 5, the latest version of Qt, enables you to develop applications with complex user interfaces for multiple targets. It provides you with faster and smarter ways to create modern UIs and applications for multiple platforms. This book will teach you to design and build graphical user interfaces that are functional, appealing, and user-friendly.